The Impact of Organizational Culture, Leadership, Self Efficacy on Employee Performance With Organizational Citizenship Behavior (OCB) As an Intervening Variable (Study on the Maha Bhoga Marga Foundation) - MANURUNG, Verasea; KOMALASARI, Yeyen; SANTOSO, Raden Tri Priyono Budi; JUNAEDI, I Wayan Ruspendi (PT Keberlanjutan Strategis Indonesia, 2024)
The research aims to explore the impact of organizational culture, leadership, self-efficacy on employee performance with Organizational Citizenship Behavior (OCB) as an intervening variable (study at the Maha Bhoga Marga Foundation). This study utilizes a quantitative approach through questionnaire methods, interviews, observations, literature review, and documentation. Data analysis will be conducted using Partial Least Squares (PLS), which is a component of the Structural Equation Modeling (SEM) framework. The research is conducted on 50 permanent employees with over 5 years of service. The results indicate that organizational culture, leadership, and self-efficacy have a positive influence on employee performance. Similarly, OCB as an intervening variable has a positive impact on employee performance by mediating organizational culture, leadership, and self-efficacy. The relationship between OCB and the phenomenon that employee performance affects organizational culture, leadership, and self-efficacy. The findings of this study are expected to contribute to a better understanding of employee performance and OCB as an intervening variable.